Escrita e reescrita de crônicas por duplas de alunos da educação de jovens e adultos: os avanços quanto aos aspectos macro textuais - Pimentel, Ana Daniela Martins Silva (2018)
This dissertation presents an investigation proposal that promotes the development of the text competence of the students of a group of Youth and Adult Education (EJA), published in the planning, textualization, modification and variant stages(DOLZ, 2010) of the chronic discursive type. The proposal was divided into modules, in a didactic sequence and carried out in a group of the 8th EJA period, which links to the 9th grade of Fundamental School, of a state public school situated in the municipality of Rio Largo, Alagoas. Its objectives are carried onward and the structure and characteristics of the chronic gender; produces a coherent description manuscript; study its text through pedagogic interventions; and reword the text itself, in an attempt to achieve the quality of writing. A textual production for formal work, evidencing an initial text and habitually subject to several versions. As a methodological procedure, we opted for action research, based on the ideas of Thiollent (1997). In addition, we seek as theoretic contributions from Antunes (2003), Marcuschi (2008), Dolz (2010) and Ruiz (2010) among others discoursing discursive genres and textual production. For data analysis, we revealed on how initial and final versions were explained by twelve doubles of students and compared an early version with a rephrased version. As intervention tools for the rewriting routing of the second version, it uses standard disks attached to the texts. The results are considered as all stages of the process of script and addition to the excellence of textual production of students.